2019
DOI: 10.3390/w11050949
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change Impact on Future Groundwater-Level Behavior Using SWAT Groundwater-Consumption Function in Geum River Basin of South Korea

Abstract: This study was to evaluate the groundwater-level behavior in Geum River Basin (9645.5 km2) of South Korea with HadGEM3-RA RCP 4.5 and 8.5 climate change scenarios and future groundwater use data using the soil and water assessment tool (SWAT). Before evaluating future groundwater behavior, the SWAT model was calibrated and validated using the daily inflows and storage of two dams (DCD and YDD) in the basin for 11 years (2005–2015), the daily groundwater-level observation data at five locations (JSJS, OCCS, BEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The groundwater level data observed by the National Groundwater Information Center (GIMS) groundwater level observation stations were collected. Five sites (BYBY, JSJS, BEMR, CASS, and OCCS) in the GRB were selected (Figure 1a) [31]. The flux tower DY, operated by K-water, is in the upper GRB within the forested area [31].…”
Section: Gis and Measured Data For Swat Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…The groundwater level data observed by the National Groundwater Information Center (GIMS) groundwater level observation stations were collected. Five sites (BYBY, JSJS, BEMR, CASS, and OCCS) in the GRB were selected (Figure 1a) [31]. The flux tower DY, operated by K-water, is in the upper GRB within the forested area [31].…”
Section: Gis and Measured Data For Swat Evaluationmentioning
confidence: 99%
“…Five sites (BYBY, JSJS, BEMR, CASS, and OCCS) in the GRB were selected (Figure 1a) [31]. The flux tower DY, operated by K-water, is in the upper GRB within the forested area [31]. The DY daily ET (mm) and soil moisture (%) data were collected from April 2011 to December 2019.…”
Section: Gis and Measured Data For Swat Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The difficulties come from complex factors that are not clearly understood or defined (Jung & Kim, 2017) and the lack of hydrological data in small rivers where stream drying usually occurs. Jung, Lee, Lee and Kim (2019) considered stream drying phenomena by applying five different factors, groundwater abstraction, afforestation, watershed development, road development, and soil erosion, and ranked their contribution rates to the loss of runoff. The results demonstrated that groundwater abstraction and forest growth had a relatively higher influence on stream drying than did other factors.…”
Section: Introductionmentioning
confidence: 99%